Ecos del deseo en el cuerpo, el enigma de la autoinmunidad (2012)
ABSTRACT: This article is the result of Autoimmune Condition and Jouissance research, carried out as part of the Master in Psychoanalytic Research of the University of Antioquia, Colombia. The purpose is to develop one of the research findings, according to which there would be a possible link between the enigmas posed by autoimmune conditions and the vicissitudes of desire which would have an echo in the body. This is based on the psychoanalytic idea of the body as a psychic territory, place of the inscription of the traces that occur in the relation to the Other, involving jouissance and desire.